Metode Latihan Vokal Pada Paduan Suara Sma Negeri 1 Rogojampi Dalam Persiapan Teen Choir Kapolresta Cup Banyuwangi: Metode Latihan Vokal - kevin ihza mahendra; tomy sugito (Universitas Negeri Surabaya, 2026)
The songs Langit Katon Biru (Blue Sky) by H. S. Parman and Kopi Dangdut (Dangdut Coffee) by Fahmi Shahab & Andi Hardi were performed by the Pramudikara Choir in preparation for the Teen Choir Kapolresta Cup Banyuwangi. This study aims to describe the vocal training methods applied to the Pramudikara Choir at SMA Negeri 1 Rogojampi and to explain their implementation in choir competitions in Banyuwangi Regency. The research method used was qualitative, with data collection techniques through observation, interviews, and documentation in the form of photographs and video recordings. The data sources for this study consisted of primary data obtained directly from the main informant, Armasari, and secondary data obtained from students participating in the Pramudikara Choir. The training process took place directly in the SMA Negeri 1 Rogojampi performance hall. The training method employed several methods, including lectures, demonstrations, and drill and practice. These methods aimed to facilitate the understanding and mastery of vocal techniques, particularly in aspects of breathing, articulation, intonation, and phrasing. The results of this training method demonstrated the effectiveness and efficiency of improving mastery of the songs Langit Katon Biru and Kopi Dangdut in preparation for the Teen Choir Kapolresta Cup Banyuwangi.